Thyroid Eye Disease: How A Novel Therapy May Change The Treatment Paradigm - Wang Y; Patel A; Douglas RS (Dove Medical Press, 2019)
Yao Wang,1 Amy Patel,1 Raymond S Douglas1,2 1Department of Surgery, Division of Ophthalmology, Cedars Sinai Medical Center, Los Angeles, CA, USA; 2State Key Laboratory of Ophthalmology, Zhongshan Ophthalmic Center, Sun Yat-sen University, Guangzhou, People’s Republic of ChinaCorrespondence: Raymond S DouglasCedars Sinai Medical Center, West Medical Office Towers, 8635 W Third St, Suite 650W, Los Angeles, CA 90048, USATel +1 310-423-8789Fax +1 310-248-8596Email raymonddouglasmd@gmail.comAbstract: Thyroid eye disease (TED) is a complex, debilitating autoimmune disease that causes orbital inflammation and tissue remodeling, resulting in proptosis, diplopia, and in severe cases, loss of vision. TED can lead to facial disfigurement and severely impact patients’ quality of life. Although the course of TED was identified over 60 years ago, effective treatment options have proved to be challenging. Current treatments such as glucocorticoid therapy and orbital radiation focus on reducing orbital inflammation. However, these therapies fail to modify the disease outcomes, including proptosis and diplopia. Recent advances in the understanding of the molecular basis of TED have facilitated the development of targeted molecular therapies such as teprotumumab, an insulin-like growth factor-1 receptor inhibiting monoclonal antibody. In recent phase 2 and phase 3 randomized placebo-controlled trials, teprotumumab rapidly achieved improvement in clinical endpoints defining TED, including improved proptosis and diplopia. Dramatic improvement in clinical outcomes achieved after teprotumumab therapy during active TED are heretofore singular and comparable only to surgical therapies achieved during the inactive phase of TED. The advent of effective medical therapy can lead to a paradigm shift in the clinical management of TED. This review will provide an overview of TED, its epidemiology, insight into the molecular biology of the disease, clinical characteristics and diagnosis, and current and emerging treatment modalities.Keywords: thyroid eye disease, proptosis, clinical activity score, insulin-like growth factor-1R, teprotumumab